Public Safety and Civil Liberties - Clutterbuck, Richard. author. aut Link
XVIII, 250 p.
Keywords: In 49 out of 50 crimes in Britain the criminals go free. Many are young and become persistent criminals. Where do the answers lie? Home environment? Education? Criminal intelligence? Technology? The law and judicial procedures? Prison or its alternatives? How can we protect civil liberties - for suspects, accused and victims?